The snake-stone - Doherty, Berlie (London : Harper Colins, 1995)
While searching for his birthmother, fifteen-year-old James, a championship diver, discovers who his real parents are and where his real home is.
"First published in Great Britain by Hamish Hamilton Ltd., in 1995"--T.p. verso.
Keywords: Birthmothers -- Juvenile fiction; Adoption -- Juvenile fiction; Diving -- Juvenile fiction